Moringa concanensis-Mediated Synthesis and Characterizations of Ciprofloxacin Encapsulated into Ag/TiO2/Fe2O3/CS Nanocomposite: A Therapeutic Solution against Multidrug Resistant E. coli Strains of Livestock Infectious Diseases - Naheed Zafar; Bushra Uzair; Farid Menaa; Barkat Ali Khan; Muhammad Bilal Khan Niazi; Fatima S. Alaryani; Kamlah Ali Majrashi; Shamaila Sajjad (MDPI AG, 2022)
Background: Multidrug resistant MDR bacterial strains are causing fatal infections, such as mastitis. Thus, there is a need for the development of new target-oriented antimicrobials. Nanomaterials have many advantages over traditional antibiotics, including improved stability, controlled antibiotic release, targeted administration, enhanced bioavailability, and the use of antibiotic-loaded nanomaterials, such as the one herein reported for the first time, appear to be a promising strategy to combat antibiotic-resistant bacteria. The use of rationally designed metallic nanocomposites, rather than the use of single metallic nanoparticles (NPs), should further minimize the bacterial resistance. Aim: Green synthesis of a multimetallic/ternary nanocomposite formed of silver (Ag), titanium dioxide (TiO2), and iron(III) oxide (Fe2O3), conjugated to chitosan (CS), in which the large spectrum fluoroquinolone antibiotic ciprofloxacin (CIP) has been encapsulated. Methods: The metallic nanoparticles (NPs) Ag NPs, TiO2 NPs, and Fe2O3 NPs were synthesized by reduction of Moringa concanensis leaf aqueous extract. The ternary junction was obtained by wet chemical impregnation technique. CIP was encapsulated into the ternary nanocomposite Ag/TiO2/Fe2O3, followed by chitosan (CS) conjugation using the ionic gelation method. The resulting CS-based nanoparticulate drug delivery system (NDDS), i.e., CIP-Ag/TiO2/Fe2O3/CS, was characterized in vitro by gold standard physical techniques such as X-ray diffractometry (XRD), field emission scanning electron microscopy (FESEM), Fourier-transform infrared (FTIR) spectroscopy. Pharmacological analyses (i.e., LC, EE, ex-vivo drug release behavior) were also assessed. Further, biological studies were carried out both ex vivo (i.e., by disk diffusion method (DDM), fluorescence-activated single cell sorting (FACS), MTT assay) and in vivo (i.e., antibacterial activity in a rabbit model, colony-forming unit (CFU) on blood agar, histopathological analysis using H&E staining). Results: The encapsulation efficiency (EE) and the loading capacity (LC) of the NDDS were as high as 94% ± 1.26 and 57% ± 3.5, respectively. XRD analysis confirmed the crystalline nature of the prepared formulation. FESEM revealed nanorods with an average diameter of 50-70 ± 12 nm. FTIR confirmed the Fe-O-Ti-CS linkages as well as the successful encapsulation of CIP into the NDDS. The zeta potential (ZP) of the NDDS was determined as 85.26 ± 0.12 mV. The antimicrobial potential of the NDDS was elicited by prominent ZIs against MDR E. coli (33 ± 1.40 mm) at the low MIC of 0.112 μg/mL. Morphological alterations (e.g., deformed shape and structural damages) of MDR pathogens were clearly visible overtime by FESEM after treatment with the NDDS at MIC value, which led to the cytolysis ultimately. FACS analysis confirmed late apoptotic of the MDR E. coli (80.85%) after 6 h incubation of the NDDS at MIC (p < 0.05 compared to untreated MDR E. coli used as negative control). The highest drug release (89% ± 0.57) was observed after 8 h using PBS medium at pH 7.4. The viability of bovine mammary gland epithelial cells (BMGE) treated with the NDDS remained superior to 90%, indicating a negligible cytotoxicity (p < 0.05). In the rabbit model, in which infection was caused by injecting MDR E. coli intraperitoneally (IP), no colonies were detected after 72 h of treatment. Importantly, the histopathological analysis showed no changes in the vital rabbit organs in the treated group compared to the untreated group. Conclusions: Taken together, the newly prepared CIP-Ag/TiO2/Fe2O3/CS nanoformulation appears safe, biocompatible, and therapeutically active to fight MDR E. coli strains-causing mastitis.